Are Odd‐Lot Orders Informed?. Issue 1 (February 2017) - Upson, James; Johnson, Hardy
Abstract: Using a version of the ITCH data set time stamped to the millisecond, O'Hara, Yao and Ye find that odd‐lot trades are highly informed. However, NASDAQ reports trades based on the size of the resting limit order, creating a bias in the count of odd‐lot trades. Using ITCH data from 2013, time stamped to the nanosecond, we find that roughly 50% of odd‐lot trades are created by the resting limit order and are part of larger marketable orders. We show that odd‐lot marketable orders are not more informed than round/mixed lot marketable orders.